PONDOK PESANTREN AND THE FORMATION OF CHARACTER STUDENTS THROUGH ACTIVITY-BASED HABITUATION: (A Case study On the Implementation of Character Education at Pesantren Pondok Iqro Bandung) (International Conference on Elementary Education, 2018)
Pesantren is an educational institution located in Indonesian society with the model of coaching that is loaded with educational values, good religious values and noble values of the nation. This study aims to (1) to know the paradigm of pesantren in shaping the character of students (2) to know the implementation of character education through activity-based habituation at Pesantren Pondok Iqro (3) to find out the factors that most dominant influence the character of students in the educational process at pesantren Pondok Iqro. The type of research conducted is the field research, while the approach used in this research is qualitative approach with case study method, in total there are 1 Kyai (elders Pesantren), 3 teachers (ustadz/ustadzah), 10 students of Pesantren Pondok Iqro were interviewed, participate in focus group discussions, and were observed. The findings of this study indicate that the Pesantren Pondok Iqro shaping the character of students in accordance with the guidance of al-Qur'an and as-Sunnah through activity-based habituation is not only done when the hours of lessons in class but also done after the hours of learning completed, there are at least 3 programs boarding activities for shaping the character of students. This research proposes a model of the formation of character education at Pondok Pesantren, which can be implemented also in public schools, that is through activity-based habituation.